Promoting healthy behaviors in preschoolers - Manoel Messias Alves de Souza; Sônia Regina Fiorim Enumo; Kely Maria Pereira de Paula; Rosangela Vieira de Souza; Rosyaline da Silva Bezerra; Katarina Bezerra Mendes (Universidade de Fortaleza, 2014)
Objective: To analyze the perception of education professionals regarding self-care behaviors displayed by preschoolers from the implementation of an education extension project as well as understand their difficulties in teaching self-care measures, assess their satisfaction with working conditions and the implementation of the education extension project. Methods: This is a descriptive, qualitative cross-sectional study conducted from September to December 2009 at the day care center "Children's House" in Petrolina, PE. A semi-structured interview was performed with eight professionals of the day care center. Data were analyzed using content analysis with emerging themes that were interpreted based on the literature concerning the theme. Results: Respondents highlighted the change in children's behavior relating to nutrition, oral and body hygiene; however, professionals lack skills and competencies to develop such actions. Conclusion: The respondents highlighted the change in children's behavior regarding self-care measures, evidencing their satisfaction; however, it was verified that they lack skills and competencies doi:10.5020/18061230.2013.p387